How culture affects ICT diffusion among SMEs in Bangladesh - Azam, Shah; Quaddus, Mohammed (ITS, 2011)
Culture is a broad spectrum of behavioural study which has been illuminated differently in different literature. Applying four cultural dimensions, power distance, uncertainty avoidance, in-group collectivism, and Bengali value, with the two fundamental antecedents of TAM, perceived usefulness and ease of use, this study attempts to look at the effects of culture in ICT diffusion among SMEs in Bangladesh. This study applies a mixed method of research approach. Following an in-depth field study which is analysed through NVivo version 9, a descriptive research design is administered to ascertain the joint impact of the study constructs. Structural equation modelling through PLS graph has been used with a cross-sectional dataset of 51 SMEs in Bangladesh collected through a questionnaire survey. The proposed model was assessed with two step procedure of measuring latent variables structural association. Prior to estimating the structural model, psychometric properties of the model, convergent and discriminant validity, were assessed. The structural model estimation results reveal a significant association of power distance and perceived ease of use with SMEs intention to use ICT. The path analysis furthered a significant effect of intention on actual ICT usage behaviour. The study concludes with implications.